Comparative Analysis of Sharing Bike Systems Based on Sustainability Indicators - HAN, Yurui; ROHMER, Serge (European Journal of Sustainable Development, 2019)
With the growing importance and widely application of the sharing bike system in public transportation systems in cities, many relevant problems emerged, which brought serious influence to the sustainable development of the system. The aim of this paper is first to research the existing sustainability indicators of urban mobility system through literature reviews, next it is to redefine and select the related indicators of sharing bike system through deeply understanding the evolution of bike sharing systems in cities from a sustainable point of view. Then, indicators are selected and applied to better understand the generations of sharing bike systems after the description of the different generations of sharing bike systems. The comparison highlights which characteristics of sharing bike system should be considered to adopt to a sustainable urban development and which features of the sharing bike system could need improvement and change to cater to active demand of the city development. Keyword: sustainability, urban mobility, sharing bike system, indicators,